Integration of APOS, RME, and Digital Learning: A Strategic Model to Enhance Computational Thinking - Trisnawati Trisnawati; Sugeng Sutiarso; Rangga Firdaus; Tina Yunarti (STAI Hubbulwathan Duri, 2025)
Computational Thinking (CT) is essential for 21st-century problem-solving but remains underdeveloped in abstract mathematics courses like linear algebra. This study addresses the gap by integrating APOS theory, Realistic Mathematics Education (RME), and digital tools into a strategic learning model to enhance CT and conceptual understanding. A Design-Based Research (DBR) approach was employed to develop, implement, and evaluate the model with 73 first-year university students enrolled in a linear algebra course at Institut Bakti Nusantara. Participants were grouped by class section into experimental (APOS–RME–digital integration) and comparison (conventional digital instruction) groups. Data were collected through pre-post CT assessments, classroom observations, surveys, and learning analytics. Students in the experimental group showed significantly higher gains across five CT components—abstraction, decomposition, algorithmic design, evaluation, and generalization—compared to the control group, with medium to large effect sizes. Improved conceptual understanding of vectors and linear transformations was also observed. Learners reported high usability and perceived instructional value, particularly in contextual and interactive tasks. Implementation challenges related to digital access and skills were mitigated through structured onboarding and offline resources. The findings demonstrate that a well-integrated APOS–RME digital model can systematically develop CT and mathematical understanding. High engagement and usability support its practical viability in higher education settings. This model offers a scalable, theory-informed framework for digital mathematics instruction. Future research should explore long-term impacts, equity strategies, and cross-institutional adoption to further enhance its applicability and sustainability.